Nonprofessional Phagocytosis Can Facilitate Herpesvirus Entry into Ocular Cells - Vaibhav Tiwari; Deepak Shukla (Clinical and Developmental Immunology)
Phagocytosis is a major mechanism by which the mediators of innate immunity thwart microbial infections. Here we demonstrate that human herpesviruses may have evolved a common mechanism to exploit a phagocytosis-like entrapment to gain entry into ocular cells. While herpes simplex virus-1 (HSV-1) causes corneal keratitis, cytomegalovirus (CMV) is associated with retinitis in immunocompromised individuals. A third herpesvirus, human herpesvirus-8 (HHV-8), is crucial for the pathogenesis of Kaposi’s sarcoma, a common AIDS-related tumor of eyelid and conjunctiva. Using laser scanning confocal microscopy, we show that successful infection of ocular cell types by all the three viruses, belonging to three divergent subfamilies of herpesviruses, is facilitated by induction of F-actin rich membrane protrusions. Inhibitors of F-actin polymerization and membrane protrusion formation, cytochalasin D and latrunculin B, were able to block infection by all three viruses. Similar inhibition was seen by blocking phosphoinositide 3 kinase signaling, which is required for microbial phagocytosis. Transmission electron microscopy data using human corneal fibroblasts for HSV-1, human retinal pigment epithelial cells for CMV, and human conjunctival epithelial cells for HHV-8 are consistent with the possibility that pseudopod-like membrane protrusions facilitate virus uptake by the ocular cells. Our findings suggest a novel mechanism by which the nonprofessional mediators of phagocytosis can be infected by human herpesviruses.